Entrepreneurial Experiments in Science Policy: Analyzing the Human Genome Project - HUANG, Kenneth G. (Institutional Knowledge at Singapore Management University, 2010)
We re-conceptualize the role of science policy makers, envisioning and illustrating their move from being simple investors in scientific projects to entrepreneurs who create the conditions for entrepreneurial experiments and initiate them. We argue that reframing science policy around the notion of conducting entrepreneurial experiments – experiments that increase the diversity of technical, organizational and institutional arrangements in which scientific research is conducted – can provide policy makers with a wider repertoire of effective interventions. To illustrate the power of this approach, we analyze the Human Genome Project (HGP) as a set of successful, entrepreneurial experiments in organizational and institutional innovation. While not designed as such, the HGP was an experiment in funding a science project across a variety of organizational settings, including seven public and one private (Celera) research centers. We assess the major characteristics and differences between these organizational choices, using a mix of qualitative and econometric analyses to examine their impact on scientific progress. The planning and direction of the Human Genome Project show that policy makers can use the levers of entrepreneurial experimentation to transform scientific progress, much as entrepreneurs have transformed economic progress.